PROSES BERPIKIR SISWA KELAS IX SEKOLAH MENENGAH PERTAMA YANG BERKEMAMPUAN MATEMATIKA TINGGI DALAM MEMECAHKAN MASALAH MATEMATIKA - Kusmayadi, Tri Atmojo; Sujadi, Imam; Muhtarom, Muhtarom (Journal of Mathematics and Mathematics Education, 2012)
Â ABSTRAKÂ This study aim to describe the studentsâ thinking process of 9th grade of Junior High School has a high mathematics capability in solving the mathematics problem based on Polya rule.This study is qualitative descriptive research. The criteria of subject selection included the studentsâ has a high mathematics capability and communication fluency both spoken and written. The data collection was done using written test and task-based interview techniques. Data analysis done based on written test data and task-based interview techniques data. And then it has been done the method triangulation to get valid subject data.Â Finally, the result of description thinking process as follows: students with high mathematics capability, in understanding problem using assimilation thinking process, make a plan using assimilation and accommodation thinking process. Assimilation thinking process can be identified when the students can mention the prerequisite material, can directly relate the sides kite (BF = FG) and can directly develop problem solving plan. Meanwhile, accommodation thinking process can be seen when the students drew an auxiliary line from E to the right thereby intersecting with CD line (the intersection was labeled H point), so devided trapezoid AEDG become right triangle EHG and rectangle AEHD. In carrying out a plan and in looking back at the completed solution, the students used assimilation thinking process.Â Keywords: thinking process, mathematics problem, and problem solving.